Behavioral Restriction Determines Left Attentional Bias: Preliminary Evidences From COVID-19 Lockdown - Lardone, Anna; Turriziani, Patrizia; Sorrentino, Pierpaolo; Gigliotta, Onofrio; Chirico, Andrea; Lucidi, Fabio; Mandolesi, Laura (Frontiers in Psychology, 2021)
During COVID-19 lockdown the individuals were forced to remain home, hence severely limiting the interaction within environmental stimuli, reducing the cognitive load placed on spatial competences. The effects of the behavioural restriction on cognition have been little examined. The present study is aimed at analysing the effects of lockdown on executive function prominently involved in adapting behaviour to new environmental demands. We analyse non-verbal fluency abilities, as indirectly provide a measure of cognitive flexibility to react to spatial changes. Sixteen students (mean age 20,75; SD 1,34), evaluated before the start of the lockdown (T1) in a battery of psychological tasks exploring different cognitive domains, have been re-assessed during lockdown (T2). The assessment included the modified Five Point Test (m-FPT) to analyse non-verbal fluency abilities. At T2, the students were also administered the Toronto Alexithymia Scale. The restriction of behaviours following a lockdown determines increased non-verbal fluency evidenced by the significant increase of the number of new drawings. We found worsened verbal span, while phonemic verbal fluency remained unchanged. Interestingly, we observed a significant tendency to use the left part of each box in the m-FPT correlated with TAS-20 and with the subscales that assess difficulty in describing and identifying feelings. Although our data was collected from a small sample, it evidences that the restriction of behaviours determines a leftward bias, suggesting a greater activation of the right hemisphere, intrinsically connected with the processing of non-verbal information and with the need to manage an emotional situation.